Ionic conductivity probed in main chain liquid crystalline azobenzene polyesters - Nardele, Chinmay G.; Dhavale, Vishal M.; Sreekumar, K.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2015)
Three main chain thermotropic liquid crystalline (LC) azobenzene polymers were synthesized using the azobenzene twin molecule (P4P) having the structure Phenylazobenzene-tetraethyleneglycol-Phenylazobenzene as the AA monomer and diols like diethylene glycol, tetraethylene glycol (TEG), and hexaethylene glycol as the BB comonomer. Terminal C(O)OMe units on P4P facilitated transesterification with diols to form polyesters. All polymers exhibited stable smectic mesophases. One of the polymers, Poly(P4PTEG) was chosen to prepare composite polymer electrolytes with LiCF3SO3 and ionic conductivity was measured by ac impedance spectroscopy. The polymer/0.3 Li salt complex exhibited a maximum ionic conductivity in the range of 10(-5) S cm(-1) at room temperature (25 degrees C), which increased to 10(-4) S cm(-1) above 65 degrees C. The temperature dependence of ionic conductivity was compared with the phase transitions occurring in the sample and it was observed that the glass transition had a higher influence on the ionic conductivity compared to the ordered LC phase. Reversible ionic conductivity switching was observed upon irradiation of the polymer/0.3 Li salt complex with alternate UV and visible irradiation. (c) 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 629-641
Keywords: azo polymers; glass transition; liquid-crystalline polymers (LCP)